KAJIAN STABILITAS PONDASI KELOMPOK TIANG PANCANG RENCANA JEMBATAN MUALAF KECAMATAN TENGGARONG - Sunanda, Arie (KURVA S JURNAL MAHASISWA, 2014)
The bridge is a transportation infrastructure that serves to connect thetwo regions that were cut off by relief or differences in contour or a flameranges such as rivers and valleys. Construction of the bridge is influenced bymany things such as the location, the position of the point of the bridge and thetype of soil at the construction site of the bridge. Muallaf bridge constructionplan is one of the main plan of the development of the existing road network inTenggarong District, Regency, where the road is planned to be an alternativeroad that connects with the road axis Tenggarong District to the District KotaBangun.In this study reviewed studies on the stability of the bridge pile foundationstake using a steel stake diameter of 400 mm, a depth of 30 meters and a plan ofthe calculation results obtained by the largest axial force axial force KN11634,33 and 1035,15 KN largest license or pile foundation is able to acceptthe style axial works. While pile experienced buckling due to lateral forces.